Futures of digital death: Past, present and charting emerging research agenda. Issue 7 (9th August 2019) - Sas, Corina; Schreiter, Miriam; Büscher, Monika; Gamba, Fiorenza; Coman, Alina
Abstract: This special issue entitled "Futures of Digital Death: Mobilities of Loss and Commemoration" explores the topic of digital death and how technologies are reconfigured by and reconfiguring social relationships with the deceased and dying loved ones as well as the larger ecosystem supporting such relationships. This Introduction article starts with an overview of the past research on digital death intended to provide a relevant context for the five papers included in this issue. Then, we reflect on how the current papers, or the present research, build on the past and can be used to address existing gaps and to inform future new research directions in order to move the field forward.